Therapy of refractory nontuberculous mycobacterial lung disease - Griffith, David E; Aksamit, Timothy R (Current opinion in infectious diseases, 2012)
The prevalence of nontuberculous mycobacterial (NTM) lung disease is increasing in the USA. Clinicians are therefore encountering these patients with increasing frequency, with the attendant multiple therapeutic challenges presented by NTM lung disease including relatively frequent (compared with tuberculosis) treatment failure. Critical elements for the successful treatment of Mycobacterium avium complex (MAC) lung disease include aggressive first therapeutic attempts and avoidance of the emergence of macrolide-resistant MAC strains, which are associated with worse treatment response and increased mortality. Reliably effective therapy for M. abscessus lung disease remains elusive but still usually requires parenteral agents. Lung resection surgery for selected patients is an important adjunct for both MAC and M. abscessus lung disease. Aside from surgery and parenteral antibiotics, there are very few data to support the efficacy of other drugs or interventions for patients who have failed the first-line therapy. Clinicians who manage NTM lung disease will inevitably encounter patients who fail the first-line therapy. The choices for effective treatment of these patients are depressingly sparse. It is critically important to avoid creation of macrolide-resistant MAC strains and to carefully choose those NTM lung disease patients who will benefit from surgery.